Evaluation of the South African Scoring System (SASS 5) Biotic Index For Assessing The Ecological Condition of the Mara River, Kenya - Oigara , Denis K.; Masese , Frank O. (African Journal of Education,Science and Technology (AJEST), 2017)
The use of rapid assessment protocols for bioassessment of streams and rivers is gaining prominence all over the world. In Africa, biotic indices are limited and only the South African Scoring System Version 5 (SASS5) has been validated for use in southern Africa. However, the popularity of SASS5 has seen its adoption for use in many countries in southern and eastern Africa, with modifications now available for Tanzania and Ethiopia. In Kenya, efforts are being made to adopt and modify SASS5 to suit local conditions. This study aimed at determining the suitability of the SASS5 protocol in the Mara River, Kenya. Macroinvertebrate samples were collected from different biotopes during the wet season to generate qualitative presence-absence and quantitative data. There were no significant differences between field-and and laboratory based site scores based on paired t-tests (p>0.05). There were significant differences in the number of taxa and ASPT Scores among sites for both field- and laboratory- based data, total SASS5 Score field data, total SASS5 Score for laboratory data ( p<0.05). There were spatial differences in site scores with headwaters sites recording higher values indicating that they were in a better ecological state compared with sites in agricultural areas and grazing areas. Some taxa such as Oligochaetae and Chironomidae were widespread and abundant, which is an indication of deteriorating water quality. The use of the SASS5 protocol in the Mara River is promising and this study shows that with modification to generate quantitative data, the findings are still comparable with the field-based qualitative approach. The advantage with the labaratory-based approach, even though it has not been widely tested, generates quantitative data that can be used in statistical analyses to identify drivers of changes in macroinvertebrate community composition.